Analisis Kesulitan Guru SD Negeri Kecamatan Keruak dalam Menerapkan K13 Materi Pembelajaran Matematika - Abidin, Zainal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to analyze the difficulties of mathematics teachers at the Public Elementary School in the Keruak sub-district in implementing the 2013 curriculum. The type of research used is mixed research. Research/Mixed Methods is a method in finding facts about the status of a group of people, an object, a condition, a system of thought, or an event with the right interpretation (Sedarmayanti & Hidayat, 2002). Data collection techniques in this study used a questionnaire filled out by respondents (elementary school teachers). Questionnaire is a data collection technique that is carried out by giving a set of questions or written statements to respondents to answer. The data from the results of calculations and data analysis,shows that there are three faktors that influence the difficulty of elementary mathematics teachers in implementing the K13 curriculum, namely the teacher faktor of 50.89%, the student faktor of 63.89%, and the faktor of the supporting facilities is 58.80%. So it can be concluded that there are three main faktors that influence the difficulty of elementary mathematics teachers in implementing K13 in each school, namely teacher faktors, student faktors, and supporting facilities faktors.